2021
DOI: 10.3390/catal11091100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cr(VI) Reduction Using Indigenous Bacterial Consortium Isolated from a Municipal Wastewater Sludge: Batch and Kinetic Studies

Abstract: Hexavalent Chromium (Cr(VI)) has long been known to be highly mobile and toxic when compared with the other stable oxidation state, Cr(III). Cr(VI)-soluble environmental pollutants have been detected in soils and water bodies receiving industrial and agricultural waste. The reduction of Cr(VI) by microbial organisms is considered to be an environmentally compatible, less expensive and sustainable remediation alternative when compared to conventional treatment methods, such as chemical neutralization and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Similar studies of Cr (VI) tolerance through reduction were observed at 3,700 mg/l at pH 7 as described by Princy et al (2020). Mixed culture could reduce Cr (VI) at concentration up to 400 mg/l as reported by Kholisa et al (2021).…”
Section: Isolation and Identification Of Chromium Tolerant Bacterial ...supporting
confidence: 83%
“…Similar studies of Cr (VI) tolerance through reduction were observed at 3,700 mg/l at pH 7 as described by Princy et al (2020). Mixed culture could reduce Cr (VI) at concentration up to 400 mg/l as reported by Kholisa et al (2021).…”
Section: Isolation and Identification Of Chromium Tolerant Bacterial ...supporting
confidence: 83%
“…The sample was then centrifuged for 10 min at 6000 rpm (2820 g ), using a Minispin® Microcentrifuge (Eppendorf, Hamburg, Germany) to remove the suspended solids. The sample was then analyzed in a UV‐vis spectrophotometer (WPA, Light Wave II, and Labotech, South Africa) at the wavelength of 540 nm, using the diphenylcarbazide (DPC) method as described by Kholisa and Chirwa 8. The total chromium in each sample was measured using a Varian AA – 1275 Series flame atomic adsorption spectrophotometer (AAS) (Varian, Palo Alto, CA, USA) at a wavelength of 359.9 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Bioremediation of Cr(VI)-contaminated environments using microorganisms appears to be a more economical and environment-friendly treatment method. The ability of bacteria to reduce Cr(VI) has been reported to depend on numerous envi-ronmental parameters that affect the transformation of Cr(VI), such as the pH and the temperature [6,7]. However, many of these studies were done in batch systems and would offer challenges on the large scale.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, water resource pollution has become more and more severe with industrialization development [1]. Heavy metal pollution due to the massive application of heavy metals in industry is gaining widespread attention [2,3]. Among them, hexavalent chromium (Cr(VI)) is often used as an essential raw material in electroplating, pigment processing, leather making, photographic, textile, and other applications.…”
Section: Introductionmentioning
confidence: 99%